DINAMIKA REPRESENTASI PERAN POLITIK BUNDO KANDUANG DALAM SISTEM PEMERINTAHAN NAGARI MODEREN DARI REPRESENTASI SUBSTANTIF MENUJU REPRESENTASI FORMAL DESKRIFTIF - Amaliatulwalidain Amaliatulwalidain (Jurnal Pemerintahan dan Politik, 2019)
This study focuses on the representation and political role Bundo Kanduang in Nagari government system. Post back to the village government, through the Regional Regulation No. 9 of 2000 on the Principles of system of village government, in accordance with the policy, which instructed about the representation Bundo Kanduang as part of the political system in the village, bahwasannya provide opportunities for role Bundo Kanduang to sit in formal government institutions in villages namely Bamus institutions and BMAS. Formal representation Bundo Kanduang today, experienced a shift in the role, as the two major constraints, among others, the non-functioning (vacuum) Institutional Bundo Kanduang as the basis of empowerment and increase political awareness Bundo Kanduang in Nagari, due to the dilemma of culture shock, to changing circumstances politics come to give effect to the erosion of the locality indigenous Minangkabau, and also very minimal attention from Sthokeholder the sustainability Institutional Bundo Kanduang, because of political understanding and sruktur politics in Nagari, generally is still held and dominated by men, so it is still difficult to providing a fitting representation space for Bundo Kanduang, and it makes sense to representation and the role of Bundo Kanduang until now have only been in the formal level descriptive. Keywords : Political Representation, Role Bundo Kanduang, Government Nagari